What is the state of the manufacturing sector in Mozambique? - Peter Simonsen Fisker; Søren Schou (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
The latest firm survey of Mozambique, the Inquerito ás Indústrias Manufactureiras (IIM) 2017, draws a concerning picture of the manufacturing sector. However, it is not obvious whether this is true for the population of manufacturing firms in Mozambique, as the representativeness of the IIM 2017 sample is not clear. This paper triangulates the findings of IIM 2017 by considering other indicators of the health of the manufacturing sector in Mozambique, including manufacturing gross domestic product, the latest enterprise census, and satellite imagery. Results indicate that the manufacturing sector grows at roughly the same pace as the population.
Keywords: 330; census; manufacturing; Mozambique; satellite images; survey